Management of Rhinophyma: Outcomes Study of the Subunit Method. Issue 3 (May 2017) - Hassanein, Aladdin H.; Vyas, Raj M.; Erdmann-Sager, Jessica; Caterson, Edward J.; Pribaz, Julian J.
Abstract : Background: Rhinophyma causes a nasal deformity and functional airway obstruction. Partial excision (eg, tangential) with secondary healing commonly removes hypertrophic soft tissues but does not improve nasal support. The subunit method for rhinophyma uses 6 nasal flaps to provide exposure for removal of rhinophymatous tissue and enhance structure. The purpose of this study was to evaluate outcomes of subunit method. Methods: Medical records of patients with rhinophyma treated with the subunit method between 2013 and 2016 were analyzed. The technique comprises degloving the distal half of the nose by elevating 6 subunit-based flaps; debulking phymatous tissues to perichondrium; enhancing nasal support with sutures/cartilage grafts; trimming excess skin; and redraping the soft tissues. Patient age, gender, need for cartilage grafts or skin grafts, revisions, and follow-up were assessed. Results: The study comprised 8 patients (6 male). Mean age was 63 years (range 34–72). All individuals had interdomal sutures for tip enhancement and 4 patients underwent cartilage grafts (alar batten) to correct external valve collapse. One patient had 2 subunits (alar) replaced with skin graft. Average follow-up was 1.6 years (range 0.2–3.7). Six patients underwent revisional procedures primarily to modify the scar between the dorsum and tip subunits. Conclusion: The subunit method addresses the 3 fundamental problems of the rhinophymatous nose: hypertrophic sebaceous tissues, excess skin, and destruction of support. Most patients may benefit from a minor revisional procedure to optimize the result. Individuals should be counseled that operation will likely require 2 stages.